2021
DOI: 10.1002/smll.202101711
|View full text |Cite
|
Sign up to set email alerts
|

SERS Quantification of Galunisertib Delivery in Colorectal Cancer Cells by Plasmonic‐Assisted Diatomite Nanoparticles

Abstract: therapies for CRC treatment, like systemic chemotherapy and immunotherapy, are expensive and invasive since they fail to target cancer cells selectively, causing severe toxicity on normal tissues besides side effects. [2][3][4][5] The epithelial-to-mesenchymal transition (EMT) is a dynamic multistep process involved in several physiological and pathological conditions, including cancer. [6] Notably, EMT in CRC is associated with an invasive, metastatic, and chemoresistant phenotype. [7] In contrast, the mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…SERS-based sensors can be used to monitor certain physiological processes as well as the real-time release of drugs in living cells [124]. Managò et al, recently demonstrated the use of hybrid nanoparticles, consisting of diatomite nanoparticles decorated with gold nanospheres and covered by a pH-sensitive gelatin shell, for label-free imaging of the nanovector localization and local SERS-sensing of the intracellular release of galunisertib in living colorectal cancer cells (see Figure 8e-g).…”
Section: Sensing Of Cellsmentioning
confidence: 99%
“…SERS-based sensors can be used to monitor certain physiological processes as well as the real-time release of drugs in living cells [124]. Managò et al, recently demonstrated the use of hybrid nanoparticles, consisting of diatomite nanoparticles decorated with gold nanospheres and covered by a pH-sensitive gelatin shell, for label-free imaging of the nanovector localization and local SERS-sensing of the intracellular release of galunisertib in living colorectal cancer cells (see Figure 8e-g).…”
Section: Sensing Of Cellsmentioning
confidence: 99%
“…In particular, it has been observed the ability of valves of several centric species to collect and confine photosynthetic active radiation (PAR) in intense hot-spots [15][16][17], and, in several cases, both valves and girdles have shown to behave like photonic crystal slabs [18,19]. Since the XIX century up to recent days, physical and chemical properties of the frustule have been exploited in several fields [20], comprising microscope objectives quality testing [7], water filtration [21], forensic science [22], optics and photonics [19,23], plasmonics [24,25], catalysis [26], biochemical sensing [27,28], solar energy harvesting [29,30], biomedicine and drug delivery [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…When an incident laser beam interacts with metallic nanostructures, plasma oscillations of metallic NPs enhance the Raman signals of molecules adsorbed or close to the metallic surface up to 6-7 orders of magnitude (15). Therefore, due to the Raman fingerprint, SERS-based sensing allows to identify and quantify molecules with excellent sensitivity and reproducibility in different environments, thereby enabling the use of the SERS technique for numerous biomedical and biosensing applications (16)(17)(18)(19)(20). Indirect SERS sensing, based on the combined use of a SERS tag and a selective aptamer-based binding, has been demonstrated for quantitative detection of endotoxins in a solution (21).…”
Section: Introductionmentioning
confidence: 99%